IMPLEMENTATION OF CHILD-FRIENDLY SCHOOL PROGRAM POLICY AT STATE HIGH SCHOOL 2 SUKABUMI CITY - Adiwijaya Barnas, Ramlan; H Suwiryo, Darmo; Hikmat, Asep; Saleh, Munandi (Penerbit Lafadz Jaya, 2023)
The implementation of the Child-Friendly School Program Policy is based on the Regulation of the Minister of Women's Empowerment and Child Protection number 8 of 2014 as an effort to fulfill the rights and protection of children in the world of education. The fulfillment of children's rights is a concept created by the Government as a strategy to determine indicators of children's rights in Child-Friendly Schools. Therefore, development and government resources are needed to support every effort aimed at ensuring the fulfillment of children's rights and protection. This study aims to determine the history of the Implementation of the Child-Friendly School Program Policy along with its supporting and inhibiting factors at State High School 2 Sukabumi City. This study used qualitative research methods and used Van Meter and Van Horn's theory with data collection through observation, interviews, and documentation. The determination of informants was carried out using snowball sampling, with 14 selected informants. Data analysis is carried out through the stages of data collection, data presentation, and conclusions. The results showed that the Implementation of the Child-Friendly School Program Policy at State High School 2 Sukabumi City was to the variables in Van Meter and Van Horn theory but the policy resource variables have not been effective, which is still a lack of facilities and infrastructure in meeting the needs of children, especially health workers assigned to the UKS room to be able to help and serve students who need health services, So that in the future it is recommended that schools can improve facilities and infrastructure as well as services to students.